Point-to-Point Iterative Learning Control with Quantized Input Signal and Actuator Faults - Huang, Yande; Tao, Hongfeng; Chen, Yiyang; Rogers, Eric; Paszke, Wojciech (1975- )
This paper applies iterative learning control to point-to-point tracking problems with a general networked structure. The data is quantized and transmitted through restricted communication channels from the controller to the actuator. Combining a logarithmic quantizer with an encoding and decoding mechanism to quantize the input signals reduces the inuence of the quantization error.
Keywords: iterative learning control; quantized input signal; encoding-decoding mechanism; optimal design; fault-tolerant